Composite risk scores and composite endpoints in the risk prediction of outcomes in anticoagulated patients with atrial fibrillation - Banerjee, Amitava; Fauchier, Laurent; Bernard-Brunet, Anne; Clementy, Nicolas; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2014)
Several validated risk stratification schemes for prediction of ischaemic stroke (IS)/thromboembolism (TE) and major bleeding are available for patients with non-valvular atrial fibrillation (NVAF). On the basis for multiple common risk factors for IS/TE and bleeding, it has been suggested that composite risk prediction scores may be more practical and user-friendly than separate scores for bleeding and IS/TE. In a long-term prospective hospital registry of anticoagulated patients with newly diagnosed AF, we compared the predictive value of existing risk prediction scores as well as composite risk scores, and also compared these risk scoring systems using composite endpoints. Endpoint 1 was the simple composite of IS and major bleeds. Endpoint 2 was based on a composite of IS plus intracerebral haemorrhage (ICH). Endpoint 3 was based on weighted coefficients for IS/TE and ICH. Endpoint 4 was a composite of stroke, cardiovascular death, TE and major bleeding. The incremental predictive value of these scores over CHADS2 (as reference) for composite endpoints was assessed using c-statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). Of 8,962 eligible individuals, 3,607 (40.2%) had NVAF and were on OAC at baseline. There were no statistically significant differences between the c-statistics of the various risk scores, compared with the CHADS2 score, regardless of the endpoint. For the various risk scores and various endpoints, NRI and IDI did not show significant improvement (≥1%), compared with the CHADS2 score. In conclusion, composite risk scores did not significantly improve risk prediction of endpoints in patients with NVAF, regardless of how endpoints were defined. This would support individualised prediction of IS/TE and bleeding separately using different separate risk prediction tools, and not the use of composite scores or endpoints for everyday ‘real world’ clinical practice, to guide decisions on thromboprophylaxis.Note: The review process for this paper was fully handled by Christian Weber, Editor in Chief.
Keywords: Cardiology; stroke prevention; thrombosis